HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN MAE GERI PADA KARATEKA DOJO TIREX KOTA PEKANBARU : - Usnul Akli; Ali Mandan; Ramadi Ramadi (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This study aims to evaluate the relationship between leg muscle explosive power and Mae Geri's speed at the Tirex karateka dojo in Pekanbaru city. Through product moment correlation test analysis, this research shows that there is a significant positive correlation between the two variables, with a significance value of 0.021 and a correlation coefficient of 0.710. These results confirm that increasing leg muscle explosive power significantly contributed to increasing Mae Geri speed in the studied karateka. The implication is that increasing leg muscle strength can be an important factor in improving the performance of kicking techniques in karate practitioners. Therefore, a deeper understanding of the relationship between muscle strength and technical ability in combat sports such as karate is relevant for the development of more effective training programs.